A green method for Nitrogen-doped graphene and its application for oxygen reduction reaction in alkaline media. (2nd January 2021) - Kakaei, Karim; Ghadimi, Golnaz
ABSTRACT: Due to the unique chemical and physical properties of graphene, as a promising material for energy conversion and storage applications, functional groups introduction on graphene surface or edges is a useful strategy for modification of its properties. For the first time, we suggest a simple, eco-friendly, and scalable for synthesising of N-rGO as a cathode material for oxygen reduction reaction (ORR) in fuel cells. An electrochemical method has been employed to investigate the mechanism of N-doping. The N-rGO electrocatalyst prepares by a one-pot electrochemical way using the raw materials of graphite rod and urea solution with DC power supply. The N-rGO had a high N content (6.8 at. %) in comparison to literature. The mechanism of N-doped reduced graphene oxide been carefully studied.